سورة الضحى وتاريخية القران في الأدبسات الاستشراقية - Abdul Rahman Hussein Obeid (Penerbit USIM, 2024)
PAPER PROCEEDINGS: THE 9TH INTERNATIONAL CONFERENCE ON QURAN AS FOUNDATION OF CIVILIZATION SWAT 2023: “AL QURAN AS A SOURCE OF REVELATION IN BUILDING A CIVILIZED SOCIETY”/ Edited by : Dr. Nadiah Ramlan, Dr. Irwan Santeri Doll Kawaid, Dr. Kauthar Abd Kadir, Nurfatin Nazilah Zainol